Autoimmune diseases involving skin and intestinal mucosa are more frequent in adolescents and young adults suffering from atopic dermatitis. Issue 12 (19th September 2017) - Cipriani, Francesca; Marzatico, Alice; Ricci, Giampaolo
Abstract: Evidence has emerged about the relationship between atopic dermatitis (AD) and autoimmune diseases, but the underlying mechanism of this association is complex and still unclear. Recent epidemiological data from the published work suggest a positive correlation. The aim of this review is to analyze the frequency of co‐occurrence of AD and autoimmune diseases. Our systematic review included 22 articles from PubMed describing the reciprocal association between AD and autoimmune diseases. Although not all the studies achieved statistically significant results, patients suffering from autoimmune diseases involving skin and intestinal mucosa, such as vitiligo, alopecia areata, celiac disease and inflammatory bowel diseases, showed a higher risk to have AD as comorbidity. In contrast, patients with rheumatological autoimmune disorders did not show a significant correlation with AD. By analyzing the occurrence of autoimmune disorders in patients with AD, we confirmed a positive correlation between AD and autoimmune diseases involving skin and intestinal mucosa, but also with systemic lupus erythematosus, while the association between AD and type 1 diabetes, autoimmune thyroiditis and rheumatoid arthritis showed conflicting results. Further investigations are need to explain the mechanism underlying the observed comorbidity between AD and autoimmune diseases and to develop targeted prevention strategies and treatment.